2017
DOI: 10.2166/nh.2017.054
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrient leaching in a fertilized juvenile hybrid aspen (Populus tremula L. × P. tremuloides Michx.) plantation cultivated in an agroforestry system in Latvia

Abstract: Leaching of macronutrients such as nitrogen, phosphorus and potassium from soils is of particular interest in the Baltic Sea region because of its adverse effects on water quality. The objective of this study was to evaluate macronutrient leaching in a juvenile hybrid aspen (Populus tremula L. × P. tremuloides Michx.) plantation cultivated in an agroforestry system and fertilized with biogas production residues, wastewater sludge and wood ash in hemi-boreal climate conditions. Analysis of macronutrient concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Digestate handling strategies have been analyzed taking into account current legislation, nutrient management planning, local agricultural constrains, and particularities such as continuous digestate production but seasonal nutrient needs in cropping systems, among others (Flotats et al, 2009). Research studies dealing with the use of fresh digestate as source of nutrients have appeared mainly linked to agricultural systems but also to some alternative areas such as hydroponics (Krishnasamy et al, 2012), forestry (Bardule et al, 2018), and soil reclamation (Garcia-Sánchez et al, 2015). Finally, the characterization of livestock-biogas-fish farming systems, which imply integration of crop production, vegetable cultivation, livestock breeding and/or fish culturing, has been addressed in developing countries, particularly in Asia (Wu et al, 2014).…”
Section: 65mentioning
confidence: 99%
“…Digestate handling strategies have been analyzed taking into account current legislation, nutrient management planning, local agricultural constrains, and particularities such as continuous digestate production but seasonal nutrient needs in cropping systems, among others (Flotats et al, 2009). Research studies dealing with the use of fresh digestate as source of nutrients have appeared mainly linked to agricultural systems but also to some alternative areas such as hydroponics (Krishnasamy et al, 2012), forestry (Bardule et al, 2018), and soil reclamation (Garcia-Sánchez et al, 2015). Finally, the characterization of livestock-biogas-fish farming systems, which imply integration of crop production, vegetable cultivation, livestock breeding and/or fish culturing, has been addressed in developing countries, particularly in Asia (Wu et al, 2014).…”
Section: 65mentioning
confidence: 99%
“…Local studies have reported the positive impact of wood ash on the radial increment of hybrid aspen plantation [11] in the first 1-2 years and additional radial increment in Forests 2022, 13,196 2 of 15 middle-aged Norway spruce stands [12] 5 years after soil improvement with fertilizers. Recent studies have also shown the impact of fertilization on soil organic carbon stock and chemical properties of the soil, groundwater, and stem wood [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The studies show a positive tree growth response in stands fertilized with wood ash (Okmanis, Kalvis, & Lazdina, 2018) and a longterm effect of initial fertilization of Norway spruce seedlings on stemwood volume (Jansons et al, 2015). Furthermore, studies focus also on environmental impacts of treatments, e.g., nutrient concentration in soil water, groundwater and surface water -after harvesting of coniferous stands (Libiete et al, 2017) and after fertilization and planting of a plantation (Bardule et al, 2018). In the context of possible fertilization induced nutrient leaching and impact on chemistry of water, it is essential to estimate the nutrient status of forest stands.…”
Section: Introductionmentioning
confidence: 99%